MEASUREMENT OF MIDSAGITTAL CORPUS CALLOSUM AREA WITH THE MODIFIED CAVALIERI METHOD IN HEALTHY RIGHT- AND LEFT-HANDED TURKISH ADULTS - Ozdikici, Mete (Malang Neurology Journal, 2020)
Background: Numerous studies have been published on the anatomy and physiology of the corpus callosum (CC). There are many contradictory studies in the literature about the changes in the size of the CC by handedness, sex, and age.Objective: This study was carried out to examine the morphometric influence of these factors (handedness, sex, and age) on the CC in healthy Turkish adultsMethods: Two hundred thirty-seven normal individuals, 101 males, and 136 females, divided into 5 age groups (20-29, 30-39, 40-49, 50-59, and 60-69) were subjected to magnetic resonance imaging (MRI) study of the brain. Of the 237 subjects, 27 males and 36 females were left-handed. Midsagittal corpus callosum area (CCA) was represented by the mean ± standard deviation of the age groups in square centimeters, and also comparisons of the right- and left-handed were also represented in Table 1. For statistical evaluation, the SPSS 15.0 was used. All statistical tests were set at a 95% confidence level (p<0.05).Results: The range of the reference values (mean values and standard deviation) for the performed measurements in the age groups and for men, women, and total are presented; and comparisons of the right- and left-handed were also represented in Table 1. In our study, CCA was found 6,46±1,05 cm2 in all men and 6,17±0,82 cm2 in all women. The values of CCA are 6,50±1,05 cm2 in right-handed men and 6,34±1,03 cm2 in left-handed men, 6,16±0,80 cm2 in right-handed women, and 6,19±0,91 cm2 in left-handed women. There is a statistically significant difference between males and females in CCA (p<0.05). There is no statistically significant difference between the age groups for CCA, and there is no difference between right- and left-handed for men and women (p>0.05) (Table 2).Conclusion: The results showed no statistical significance of the effect of age or handedness on the surface area of the CC. However, it was statistically significant that the size of men's CC was higher than that of women.Keywords: Midsagittal corpus callosum area, modified Cavalieri method, handedness, Turkish adults, magnetic resonance imaging.